LATANZA PRODUCTION'S LIVE STREAMING STRATEGY IN PROMOTING CONSUMER PRODUCTS - Yushita, Tiara Putri; Purwanto, Alif Irsa; Nurfalah, Farida; Andriany, Dian (Penerbit Lafadz Jaya, 2024)
Live Streaming is currently phenomenal in promoting its special products through YouTube. This research aims to explore how Latanza Production's uses a Live Streaming strategy to promote its consumer products. The Research Object Involves Latanza Production's Owner and Latanza Production's Consumer, using the Proposive Sampling Technique. The analysis method used is qualitative, with data collection through observation, interviews, and documentation. The analysis highlights Latanza Production's socialization in promoting consumer products through planning, communication, and evaluation. The theory used is Anwar Arifin's theory, by identifying four indicators: Determining the Audience, Determining the Message, Determining the Live Streaming Method, and Selection of Youtube Use and Media. The results of the study show that strategies are very important to achieve the goal, the researcher explores the promotion obstacles faced including fierce competition, and technical problems during live broadcasts, while efforts in Live Streaming to build trust are very important because internet media cannot present the atmosphere and products as experienced in the live shopping experience. The study highlights the importance of innovation and adaptation in communication strategies to fully harness the potential of these social media and streaming technologies with social and live streaming. Social media, especially platforms like YouTube, has become an integral part of everyday life, influencing people's behavior and culture